2019
DOI: 10.1186/s12882-019-1226-0
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous pulse methylprednisolone for induction of remission in severe ANCA associated Vasculitis: a multi-center retrospective cohort study

Abstract: Background Intravenous pulse methylprednisolone (MP) is commonly included in the management of severe ANCA associated vasculitis (AAV) despite limited evidence of benefit. We aimed to evaluate outcomes in patients who had, or had not received MP, along with standard therapy for remission induction in severe AAV. Methods We retrospectively studied 114 consecutive patients from five centres in Europe and the United States with a new diagnosis of severe AAV (creatinine > 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 25 publications
(23 reference statements)
0
46
0
4
Order By: Relevance
“…Our findings therefore align with those of a recent retrospective analysis of short-term outcomes in severe renal AAV. In this group, IV methylprednisolone use was associated with increased risks of infection and diabetes (and not with any differences in patient or renal survival) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings therefore align with those of a recent retrospective analysis of short-term outcomes in severe renal AAV. In this group, IV methylprednisolone use was associated with increased risks of infection and diabetes (and not with any differences in patient or renal survival) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in younger patients have shown an association between organ damage and higher cumulative doses and longer duration of glucocorticoid use (10,12). A recently published retrospective study of patients with severe AAV with renal involvement found an association between treatment with intravenous methylprednisolone and higher incidence of diabetes mellitus (20), one of the damage items considered as treatment-related.…”
Section: Discussionmentioning
confidence: 99%
“…The median initial hospital period was 18 days (IQR[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], and during the first year 69.1%(114/165) of the patients were readmitted to hospital, with a median stay of 12 days (IQR 6-31). Median total hospital stay (including initial stay) during the first year was 31 days (IQR 17-50).…”
mentioning
confidence: 99%
“…Previous studies have found associations between long duration of glucocorticoid use, especially in higher doses, and total organ damage [24,267]. Associations have also been reported between duration of glucocorticoids and cataract [267], and between treatment with intravenous methylprednisolone and development of diabetes mellitus [268,269].…”
Section: Figure 7 Vasculitis Damage Index Itemsmentioning
confidence: 96%